TINJAUAN HUKUM ISLAM MENGENAI LARANGAN WALIMAH AL ‘URSH SELAIN MUSIM PANEN MENURUT ADAT DESA SIDOKUMPUL SAMBENG LAMONGAN - Mohammad Majduddin; M Muizzuddin (Institut Keislaman Abdullah Faqih Gresik, 2019)
Abstract: This study aims to determine a review of Islamic law regarding the practice of wali mah al-'ursh according to community customs in Sidokumpul Village and the background of the traditional practice of wali mah al-'ursh in Sidokumpul Village Sambeng District, Lamongan Regency. This research was examined as a case study in Sidokumpul Village, Sambeng District, Lamongan Regency, the data collection of this study used the Qualitative Interviews technique to the leaders and community of Sidokumpul village, Qualitative Observation in the village environment and walimah events, Qualitative Documents and analyzed with phenomenological analysis. The results of this study indicate that the things that underlie the practice of walimah in Sidokumpul Village are due to lack of economic factors, so that if it is carried out other than the harvest season there will be social inequalities which will result in disruption of harmony between residents. Because the local community prioritizes Social Principles in everyday life. as well as in the view of the customary Islamic law of Walimatul 'ursy in Sidokumpul Village does not contradict Islamic law because there is absolutely nothing contradicting Nash either the Al-Qur'an or Al-hadith.Keywords: Walimatul 'ursy, Islamic law, local community